Bilateral pheochromocytoma/intra-adrenal paraganglioma in von Hippel-Lindau patient causing acute myocardial infarction - Bachurska, Svitlana; Staykov, Dmitriy; Belovezhdov, Veselin; Sasano, Hironobu; Gulinac, Milena; Stefanov, Chavdar; Neumann, Hartmut P.H. (Polish Journal of Pathology, 2014)
A 26-year-old male presented to the emergency department complaining of obstipation, severe headache and abdominal pain. An autopsy revealed bilateral pheochromocytoma and acute myocardial infarction. The tumor cells showed positive immunoreactivity of both chromogranin A and synaptophysin and were negative for adrenocortical markers such as SF-1, c17, scc, 3-HSD as well as SDHB, suggesting a germline mutation of the gene SDHB or SDHD. Molecular genetic analyses did not show a mutation in these two genes, but a mutation in the VHL gene, in exon 3: VHL c.499C>T. This is a missense mutation and causes an amino acid change (Arg167Trp).